Development of Arduino based Omni Wheel Plotter - N, Karthik; Nagraaj, Abhijeet (International journal of recent technology and engineering, 2020)
This project demonstrates and tests the feasibility of an omni wheel plotter, where plotters are used to obtain the vector and line drawings of engineering models. The plotters developed before were having rigid frame, bulky and. many of the plotters developed for academic purpose are for research purpose having less flexibility or constrained to a large extent. In this project, a plotter is developed which does not contain any rigid frame. Instead it uses a movable frame with omni wheels attached to it for mobility. The use of omni wheels makes the design of chassis or frame easy. To further simplify the design, a pivot joint suspension is built into it. The electronics part of the plotter consists of an Arduino Uno microcontroller board, ULN2003 stepper motor driver and a PCB to provide the power for running the motor drivers. The ‘G’ and ‘M’ codes are used to plot the required figure by the plotter. All connections were first designed and tested on a software called Fritzing. For programming the ‘Uno’ microcontroller, software provided by Arduino is used. The codes are communicated to the plotter with the help of HC-05 Bluetooth module. For sending these commands, a software called Coolterm is used. All software’s used for design, fabrication and coding of the electronics is based on open source license, while the chassis has been designed using SolidWorks software. These plotters can be used for plotting 2D figures and PCB circuits, they can also be used for cutting 2D shapes and removal of excess material by replacing the pen with suitable cutting tool or laser cutters.